Extent of Execution of P.E. Administrators’ Functions as Influenced by Their Leadership Capabilities in an Engineering University in China - Han, Changsong (Pacific International Journal, 2024)
This study explores the relationship between leadership capabilities and management functions of Physical Education (PE) administrators at Hubei Engineering University, China. Using a descriptive-comparative-correlational research design, data were collected from PE teachers to assess the effectiveness of administrators in strategic planning, organizing, directing/leading, and controlling. Additionally, leadership capabilities such as organizational direction, collaborative leadership, and instructional leadership were evaluated. The results revealed that administrators are generally effective in their management functions, with organizing and collaborative leadership receiving the highest scores. However, challenges related to resource management and internal control systems were identified. Significant correlations between management functions and leadership capabilities underscore the importance of strong organizational skills for effective leadership. These findings provide insights into the leadership development needs of PE administrators and suggest practical solutions for overcoming administrative challenges.